Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1074/jbc.ra118.006819
|View full text |Cite
|
Sign up to set email alerts
|

The human innate immune protein calprotectin induces iron starvation responses in Pseudomonas aeruginosa

Abstract: Most microbial pathogens have a metabolic iron requirement, necessitating the acquisition of this nutrient in the host. In response to pathogen invasion, the human host limits iron availability. Although canonical examples of nutritional immunity are host strategies that limit pathogen access to Fe(III), little is known about how the host restricts access to another biologically relevant oxidation state of this metal, Fe(II). This redox species is prevalent at certain infection sites and is utilized by bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
162
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(197 citation statements)
references
References 65 publications
(87 reference statements)
33
162
2
Order By: Relevance
“…The rewiring of metabolic networks that is suggested by our proteomics study also appears to contribute to alterations in virulence factor production. We show that iron starvation downregulates several proteins in the phenazine biosynthesis proteins, consistent with reduced phenazine production upon iron starvation, as observed by Zygiel et al in a recent study performed under similar conditions (51). Previous work demonstrated the phenazines play a role in biofilm development by reducing ferric iron to ferrous iron, thereby aiding in iron acquisition (74).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The rewiring of metabolic networks that is suggested by our proteomics study also appears to contribute to alterations in virulence factor production. We show that iron starvation downregulates several proteins in the phenazine biosynthesis proteins, consistent with reduced phenazine production upon iron starvation, as observed by Zygiel et al in a recent study performed under similar conditions (51). Previous work demonstrated the phenazines play a role in biofilm development by reducing ferric iron to ferrous iron, thereby aiding in iron acquisition (74).…”
Section: Discussionsupporting
confidence: 90%
“…6A) (50). These data are consistent with recently published work showing that phenazine metabolites are reduced upon iron starvation mediated by the host innate immune protein calprotectin (51). The amino acid sequences of the enzymes encoded by the two phz operons are 100% identical from PhzC to PhzG, so only PhzA1/A2 and PhzB1/B2 could be differentiated by proteomic analysis.…”
Section: Proteomics Reveals Broad Changes In Metabolic Proteins Upon supporting
confidence: 89%
“…The immune protein calprotectin has been shown to play a critical role in hampering the progress of infections associated with pathogens occupying a range of host niches, including Staphylococcus aureus, Helicobacter pylori, Candida albicans, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterococcus faecalis (32,(56)(57)(58)(59)(60). Though earlier reports suggested that calprotectin was incapable of binding Fe in the host environment, new evidence has emerged indicating that calprotectin can starve bacteria for iron in selected media as well as under certain in vivo conditions (3,32,43,(56)(57)(58)(59)(60)(61)(62). Importantly, enzymatic function of the S. mutans superoxide dismutase (SOD) is heavily dependent on Mn for protection from oxidative stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, bacterial relationships are also shaped by the presence of other host proteins involved in the immune response. Calprotectin, a protein released from neutrophils or other phagocytes, sequesters essential nutrients including iron, zinc, and manganese away from bacteria in order to inhibit their growth (Zygiel et al, 2019). Iron-, zinc-, and manganese-limited environments in turn repress the production of anti-staphylococcal factors in P. aeruginosa, promoting increased levels of P. aeruginosa and S. aureus cocolonization in vitro and in vivo (Wakeman et al, 2016).…”
Section: Enhanced Tolerancementioning
confidence: 99%